Catalytic Activity and Kinetic Modeling of Various Modules HZMS-5 and Treated MCM-41 Catalysts, for the Liquid-Phase Ketalization of Glycerol With Acetone - Alsawalha, Murad (Frontiers in Chemistry, 2019)
Studies of the Ketalization reaction using trivalent alcohol glycerol in combination with acetone and their kinetics modeling are still limited. The focus of this current study is an investigation into HZSM-5 with various silica to alumina molar ratios (M = 35, 90, and 160) for the reaction between glycerol and acetone. In addition, the influence of reaction temperatures (25, 50, and 60°C) on the rate of the reaction have also been considered. Additionally, this investigation established the rate law for all HZMS-5 models (M = 35, 90, and 160) which showed “n” order equals half while the activation energy was found to be 164.34 kJ mol−1 with a constant reaction rate of k0 = 5.2678*1028 (Concentration1/2. min-1). Furthermore, MCM-41 pure mesoporous materials were separately treated using various methods. The first involved treatment using Dichlorodimethylsilane MCM 41(TD) and later treatment of a pure sample with sulfuric acid MCM-41. The sulfated MCM-41 sample (MCM41-SU) showed that reaction order equals n = −1 and a rate constant of (k) = 3.9 × 102 (Concentration−2. min−1). A close correlation and agreement was found between the experimental modeling and the theory. Additionally, this current kinetic study showed that water production has no effect on the conversion activity within 10 min from the start of reaction. Besides, further kinetics investigations were performed to ascertain the estimated time for water production based on the conditions applied during the reaction system. It resulted in an average time of 3 min for equilibrium to be reached in the reaction system. It was found that the estimated reaction equilibrium time (teq) is within the range from zero to 10 min in agreement with the proposed kinetic model in this work. Finally, it was also observed that a low equilibrium conversion (XAeq) had been obtained in the present work about 0.42 (42%). At a reaction temperature of 60°C (333.15 K) and at one atmosphere, the acetone was shown to exert a vapor pressure of about 113.737 mm Hg. Hence, the overall order of the reaction was determined by the method of initial rates. Similarly, in order to ascertain the dispersion of aluminum, together with its distribution on the surface of a catalyst for a zeolite that has varying molar ratios of silica to alumina as is the case for example with ZSM-5 (35), a mathematical approach is proposed in this study for its calculation.